2010
DOI: 10.1111/j.1600-051x.2010.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Periodontal disease and pre‐eclampsia: a systematic review

Abstract: A literature search of PubMed, EMBASE and CINAHL until August 2010 revealed 12 eligible observational studies and three randomized-controlled trials (RCTs). It appeared difficult to compare these studies, due to variations in definitions of periodontal disease and pre-eclampsia, timing of periodontal examination and inadequate control for confounding factors. Eight observational studies reported a positive association, while four studies found no association. None of the RTCs reported reductions in pre-eclampt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 95 publications
(196 reference statements)
0
39
0
9
Order By: Relevance
“…Periodontitis could act as a source of bacteria and inflammatory mediators such as interleukins, tumour necrosis factor and prostaglandin E2 (PGE2) that leads to the severity of periodontal breakdown. Daily episodes of bacteraemia or dissemination of bacterial endotoxins originating from the periodontal focus may enter the bloodstream, disseminate throughout the body and trigger the induction of systemic inflammatory responses [23]. These results indicate that progression of maternal periodontal disease during pregnancy increases the risk for preeclampsia, which is considered as a major obstetric complication resulting in preterm delivery.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Periodontitis could act as a source of bacteria and inflammatory mediators such as interleukins, tumour necrosis factor and prostaglandin E2 (PGE2) that leads to the severity of periodontal breakdown. Daily episodes of bacteraemia or dissemination of bacterial endotoxins originating from the periodontal focus may enter the bloodstream, disseminate throughout the body and trigger the induction of systemic inflammatory responses [23]. These results indicate that progression of maternal periodontal disease during pregnancy increases the risk for preeclampsia, which is considered as a major obstetric complication resulting in preterm delivery.…”
Section: Discussionmentioning
confidence: 85%
“…In another review, the results of observational studies and RCTs investigating the relationship between periodontal disease and preeclampsia. It shows that an association between periodontal disease and preeclampsia was noticed [23]. Also, in the presence of preeclampsia, periodontal disease may be an additional burden that further increases the risk for preterm delivery [8].…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Despite the significant association between periodontal disease and preeclampsia, periodontal therapy during pregnancy has not been effective in reducing the rate of preeclampsia. 85 Furthermore, one study has examined the presence of microbes in amniotic fluid in preeclamptic women and concluded that the low presence of microbes and intra-amniotic infection plays a limited role in the incidence of preeclampsia. 84 …”
Section: The Human Microbiome and Pregnancy Outcomesmentioning
confidence: 99%
“…Due to its chronic inflammatory/bacterial infection nature, P has been epidemiologically linked to multiple systemic diseases such as cardiovascular diseases, diabetes, rheumatoid arthritis, preeclampsia, preterm birth and inflammatory bowel disease [2][3][4][5][6]. These pathological conditions could share common pathophysiological pathways with P, especially the incriminating role of PC and their effect on defense or endothelial cells.…”
Section: Introductionmentioning
confidence: 99%